A comparison of deaf and hearing subjects in visual nonverbal sensitivity and information processing. - Rollman SA; Harrison RD (American Annals of the Deaf, 1996)
This investigation compared deaf and hearing subjects in the degree of accuracy with which they can perceive visual nonverbal information about people, their short-term recall of visual information and the extent to which they focus on different parts of the body. Subjects were asked to gauge information about relationships between people shown in photographs and later to indicate what they remembered from the photos. Neither group demonstrated a statistically significant advantage in accuracy or recall. When comparing the reasoning processes used by the two groups to arrive at their conclusions it was found that deaf subjects were more than twice as likely as hearing subjects to base their judgments upon hand and arm behavior.